A Stretchable Capacitive Strain Sensor Having Adjustable Elastic Modulus Capability for Wide‐Range Force Detection. Issue 3 (17th December 2019) - Cao, Peng-Juan; Liu, Yiwei; Asghar, Waqas; Hu, Chao; Li, Fali; Wu, Yuanzhao; Li, Yunyao; Yu, Zhe; Li, Shengbin; Shang, Jie; Liu, Xincai; Li, Run-Wei
Abstract : Stretchable strain sensors are important components of soft robotics, rehabilitation assistance, and human health monitoring systems. However, strain sensors capable of wide‐range force detection with adjustable modulus facilities are highly desirable to obtain mechanical feedback in various scenarios. Herein, a stretchable capacitive strain sensor capable of adjustable modulus and wide‐range force detection is reported. The sensor consists of two liquid metals (LMs) filled thermoplastic elastomer (TPE) tubes encapsulated in flexible silicone. The adjustable modulus capability of the sensor is attained by mounting the sensor with springs of different elastic coefficients. During electromechanical tests, the elastic coefficient‐dependent adjustable modulus is obtained in the range of 0.78–10.3 MPa. After optimizing the performance, a sensor capable of wide force‐sensing range (0.07–74 N), high cyclic stability (>3500 cycles), with low hysteresis, good linearity, and fast response time (<50 ms) is achieved. Finally, a digital display system is developed to display the amount of detected force during the loading of the sensor, which confirms the great capability of the sensor to be applied in joint rehabilitation and soft robotic fields. Abstract : A stretchable capacitive strain sensor with adjustable elastic modulus is prepared by mounting various springs with the sensor. The load‐carrying capacity of the spring‐mounted sensor has increased more than ten times as compared with the sensor without the spring. A local built strain‐measuring system is used, which successfully measured the wide‐range force during the loading of the sensor.